2001
DOI: 10.1074/jbc.m102034200
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-dependent Kinases cdk2 and cdk5 Act by a Random, Anticooperative Kinetic Mechanism

Abstract: cdk2⅐cyclin E and cdk5⅐p25 are two members of the cyclin-dependent kinase family that are potential therapeutic targets for oncology and Alzheimer's disease, respectively. In this study we have investigated the mechanism for these enzymes. Kinases catalyze the transfer of phosphate from ATP to a protein acceptor, thus utilizing two substrates, ATP and the target protein. For a two-substrate reaction, possible kinetic mechanisms include: ping-pong, sequential random, or sequential ordered. To determine the kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
4
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 63 publications
0
36
4
1
Order By: Relevance
“…Consistent with these data it has been shown that active CDK4/CycD1 complex cannot be readily reconstituted by mixing recombinant CDK4 and cyclin D (2). Unlike CDK2/cyclin A (34), CDK4 does not appear to spontaneously activate when bound to cyclin D and exhibits ordered addition kinetics (35,36). Phosphorylation studies using peptidic or Rb-protein substrates reveal a low specific activity of CDK4/cyclin D1 versus peptides and a modulation of the enzymatic K m for ATP (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these data it has been shown that active CDK4/CycD1 complex cannot be readily reconstituted by mixing recombinant CDK4 and cyclin D (2). Unlike CDK2/cyclin A (34), CDK4 does not appear to spontaneously activate when bound to cyclin D and exhibits ordered addition kinetics (35,36). Phosphorylation studies using peptidic or Rb-protein substrates reveal a low specific activity of CDK4/cyclin D1 versus peptides and a modulation of the enzymatic K m for ATP (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…1, corresponding to unordered (random) substrate binding (10). [There is evidence that this is the mechanism driving at least some cyclin-dependent kinase-catalyzed phosphorylation reactions at the heart of the cell cycle (11). ]…”
Section: A Motivational Examplementioning
confidence: 99%
“…So far, numerous specific CDK inhibitors have been identified on the basis of their ability to inhibit CDK1, CDK2 or CDK4: the purines olomoucine (Vesely et al, 1994), roscovitine de Azevedo et al, 1997); purvalanols (Gray et al, 1998;Chang et al, 1999;Villerbu et al, 2002), CVT-313 (Brooks et al, 1997), C2-alkylynated purines (Legraverend et al, 2000), H717 (Dreyer et al, 2001) and NU2058 (Arris et al, 2000), piperidine-substituted purines (Shum et al, 2001), toyocamycin (Park et al, 1996), flavopiridol (Losiewicz et al, 1994), indirubins (Hoessel et al, 1999;Leclerc et al, 2001), paullones Zaharevitz et al, 1999;Leost et al, 2000), g-butyrolactone (Kitagawa et al, 1993), hymenialdisine , indenopyrazoles (Nugiel et al, 2001), the pyrimidines NY6027 (Arris et al, 2000) and CGP60474 (Zimmermann, 1995), pyridopyrimidines (Barvian et al, 2000), the aminopyrimidine PNU 112455A (Clare et al, 2001), oxindoles (Kent et al, 1999;Davis et al, 2001), PD0183812 (Fry et al, 2001), cinnamaldehydes (Jeong et al, 2000), quinazolines (Shewchuk et al, 2000;Sielecki et al, 2001), fasclaplysin (Soni et al, 2000(Soni et al, , 2001, SU9516 (Lane et al, 2001) and benzocarbazoles (Carini et al, 2001). Despite their chemical diversity, these inhibitors all act by competing with ATP at the ATP-binding site of the kinase.…”
Section: Introductionmentioning
confidence: 99%